2012
DOI: 10.1111/j.1440-1843.2011.02115.x
|View full text |Cite
|
Sign up to set email alerts
|

Association between soft drink consumption and asthma and chronic obstructive pulmonary disease among adults in Australia

Abstract: Background and objective: The aim of this study was to examine the association between soft drink consumption and self-reported doctor-diagnosed asthma and COPD among adults living in South Australia. Methods: Data were collected using a risk factor surveillance system. Each month a representative random sample of South Australians were selected from the electronic White Pages and interviews were conducted using computer-assisted telephone interviewing (CATI). Results: Among 16 907 participants aged 16 years a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
57
1
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(63 citation statements)
references
References 26 publications
2
57
1
3
Order By: Relevance
“…Oxidative stress (2,3,6,8,9,(13)(14)(15) pertaining to PD may be mediated through advanced glycation end-products that are created through non-enzymatic pathways from monosaccharide substances, dicarbonyls originating from the Maillard reaction, sugar self-oxidation and other molecular pathways (16,17) . Several studies show a link between soft drinks and systemic disease (18,19) , but the specific association between the intake of soft drinks and PD has not been investigated yet. From the aspect of epidemiology, it is therefore of interest to assess the association between the intake of soft drinks and PD through a large-scale epidemiological study.…”
mentioning
confidence: 99%
“…Oxidative stress (2,3,6,8,9,(13)(14)(15) pertaining to PD may be mediated through advanced glycation end-products that are created through non-enzymatic pathways from monosaccharide substances, dicarbonyls originating from the Maillard reaction, sugar self-oxidation and other molecular pathways (16,17) . Several studies show a link between soft drinks and systemic disease (18,19) , but the specific association between the intake of soft drinks and PD has not been investigated yet. From the aspect of epidemiology, it is therefore of interest to assess the association between the intake of soft drinks and PD through a large-scale epidemiological study.…”
mentioning
confidence: 99%
“…It is also possible that the link between SSB consumption and asthma is moderated by excess adiposity, as SSB intake increases the risk of obesity (15) and obesity is highly correlated with asthma (29) . However, the study by Shi et al (7) found that the relationship between SSB consumption and asthma held even when controlling for body composition. Thus, there appear to be other important factors besides obesity that may explain the connection between SSB and asthma development.…”
Section: Discussionmentioning
confidence: 92%
“…SSB daily, as compared with those who did not consume SSB (7) . With regard to children, Stensson et al (17) investigated the relationship between oral health and asthma in 127 asthmatic and 117 matched, non-asthmatic pre-school children.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations